Replenishment Cost of a Storage System Modelled through a Defective Renewal Equation - Ferreira, M. A. M. (arXiv:2110.01987, 2025)
A storage system where a k units stock is replaced instantaneously, when required,is presented in this work. It is also supposed a Poisson demand. It is proved that the storage system replenishment cost expected present value function fulfills a defective renewal equation, being proposed for it an asymptotic expression.